METHOD FOR EVENING ASTRONOMIC OBSERVATIONS - Sheroz Eraliyevich Nurmamatov (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the method of organizing astronomy laboratories and observations in general secondary schools. At the same time, we discussed how practical observations can be made in astronomy, and their types.